2008
DOI: 10.1163/156855508x363861
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Co-polymers of N-Phenyl Methacrylamide With Glycidyl Methacrylate

Abstract: Co-polymers of N-phenyl methacrylamide and glycidyl methacrylate of different compositions were synthesized by free radical solution co-polymerization of the monomers in dimethylformamide using benzoyl peroxide as the initiator at 70 • C. Solubility of the co-polymers was tested in various solvents. The molecular structure of the co-polymers was elucidated by infrared and proton nuclear magnetic resonance spectroscopy. The composition of the co-polymers was determined from their 1 H-NMR spectra by using the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Consistent with the result of Reddy et al. (2008), we find that the two distributions are very similar at net Ly EWs 0 Å, but there is a sharp drop off at toward higher values of net Ly EW that is largely responsible for the difference in overall mean net Ly EW between the two samples.…”
Section: Analysis and Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with the result of Reddy et al. (2008), we find that the two distributions are very similar at net Ly EWs 0 Å, but there is a sharp drop off at toward higher values of net Ly EW that is largely responsible for the difference in overall mean net Ly EW between the two samples.…”
Section: Analysis and Resultssupporting
confidence: 91%
“…Reddy et al. (2008) showed that the ratio of strong emitters to absorbers for LBGs at redshifts is approximately the same as for those selected by the same set of colour criteria at (see the respective population statistics in Table 6). Thus, there is no underlying selection bias of aLBGs versus eLBGs that could affect the segregation properties in the different redshift ranges.…”
Section: Analysis and Resultsmentioning
confidence: 92%
See 3 more Smart Citations